The Development of Problem Based Learning (PBL) Student Worksheets (Lkpd) in IPAS Learning of Sound Material and its Properties for Grade V SDN 09 Sitiung - Yulia Darniyanti; Muhammad Subhan; Dini Puspita Sari (The Future of Education Journal, 2024)
Education is very important for humans in all aspects of their lives. Education is something that is necessary and important to instill in every individual. With education, a person can experience a teaching process to shape character, responsibility and moral formation. Furthermore, through education, the development of human personality can be directed to a better place. Humans can grow and develop through education, because humans can grow and develop through a natural process towards maturity, both physical and spiritual. This research uses a type of research and development or Research and Development (R&D), which is a form of research that aims to create products, both new products and modified ones from previously existing products. The development model used in this research is ADDIE which consists of 5 stages: analysis, design, development, implementation and evaluation. The development process carried out is the Validity Test stage. Based on the development of Student Worksheets (LKPD) Based on Problem Based Learning (PBL) in Science and Science Learning, Sound Material and Its Properties for Class V SDN 09 Sitiung, it can be concluded as follows: development of Student Worksheets (LKPD) Based on Problem Based Learning (PBL) in Science and Technology Learning Sound Material and Its Properties for Class V SDN 09 Sitiung uses the ADDIE development model which can be tested in class V SDN 09 Sitiung; and validation of the development of Student Worksheets (LKPD) Based on Problem Based Learning (PBL) in Science and Science Learning Sound Material and Its Properties for Class V SDN 09 assessed by 3 expert validators. These validators are 3 UNDHARI lecturers.